Synthesis of Some Bis-azo Pyrazolone Acid Dyes and Their Application on Wool, Silk and Nylon - Bhavasar, R.A.; Desai, C.M. (Asian Journal of Chemistry, 2010)
Monoazo pyrazolone dyes are very common but bisaw pyrazolone dyeswith arylazo group in position-4 and second arylazo group at position -4of phenyl nucleus are not available in literature. Firstly aryldiazoniumchloride is coupled in position-4 in alkaline medium and the second aryldiazogroup in position-4' of 1-phenyl group in acidic medium.